Reforming Land Acquisition Law to Promote Sustainable Investment in Indonesia: Balancing Economic Growth and Community Rights: Mereformasi Hukum Pengadaan Tanah untuk Mendorong Investasi Berkelanjutan di Indonesia: Menyeimbangkan Pertumbuhan Ekonomi dan Hak-Hak Masyarakat - Pandapotan Damanik (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Land acquisition is essential to infrastructure development and economic activity, yet its administration must simultaneously guarantee legal certainty, social justice, and environmental responsibility. Specific Background: Indonesia has established a regulatory framework through agrarian, spatial planning, public-interest development, and job creation legislation, but implementation remains constrained by overlapping tenure claims, compensation disputes, fragmented administration, and agrarian conflict. Knowledge Gap: Existing studies largely examine statutory implementation, infrastructure acceleration, or dispute settlement separately, leaving limited integrated analysis connecting legal renewal, sustainable investment, and the protection of affected populations. Aims: This normative legal study analyzed the Indonesian land acquisition framework, identified its principal legal challenges, and formulated a regulatory direction that reconciles economic development with societal protection. Statutory, conceptual, and comparative approaches were applied to legislation and academic literature through qualitative analysis. Results: The existing framework provides a basis for legal certainty, but uncertain ownership status, weak public participation, inadequate recognition of indigenous peoples, disputed valuation, and limited socioeconomic recovery remain substantial barriers. Priority measures include regulatory harmonization, integrated digital administration, accessible dispute resolution, meaningful consultation, transparent valuation, livelihood restoration, non-cash compensation options, and Environmental, Social, and Governance integration. Novelty: The study constructs an integrated legal framework linking tenure certainty, participatory justice, socioeconomic recovery, digital governance, and sustainability principles. Implications: These measures can support a more transparent, inclusive, accountable, and socially just system while reducing agrarian disputes and strengthening long-term development certainty. Highlights: Regulatory harmonization and digital administration address overlapping tenure and spatial records. Meaningful consultation, livelihood restoration, and flexible compensation strengthen social justice. Restorative dispute resolution and transparent governance reduce agrarian conflict and legal uncertainty. Keywords: Land Acquisition, Sustainable Investment, Legal Reform, Legal Certainty, ESG.